Islamic piety in medieval Syria : mosques, cemeteries and sermons under the Zangids and Ayyūbids (1146-1260) - Talmon-Heller, Daniella. (Jerusalem Studies in Religion and Culture, 2007)
A study of religious thought and practice across a broad social spectrum, but within a well-defined historical context, this book is an interdisciplinary endeavor that incorporates the tools of philology, social-history and historical-anthropology. Focusing on the mosques, public assemblies, cemeteries and shrines of Syrian Muslims in the period of the crusades and the anti-Frankish jihad, the book describes and deciphers religious rites and experiences, liturgical calendars, spiritual leadership, and perceptions of impiety and dissent. Working from a perspective that breaks down the dichotomization of religion into 'official' and 'popular,' it exposes the negotiation, construction and dissemination of hybrid forms of religious life. The result is an intimate and complex presentation of the texture of medieval Islamic piety.